Low-dose dobutamine in acute myocardial infarction with intermediate to high risk of cardiogenic shock development (the DOBERMANN-D trial): study protocol for a double-blinded, placebo-controlled, single-center, randomized clinical trial - Sarah Louise Duus Holle; Joakim Bo Kunkel; Christian Hassager; Redi Pecini; Sebastian Wiberg; Pernille Palm; Lene Holmvang; Lia Evi Bang; Jesper Kjærgaard; Jakob Hartvig Thomsen; Thomas Engstrøm; Jacob Eifer Møller; et al. (Trials)
Abstract Background Cardiogenic shock (CS) occurs in 5–10% of patients with acute myocardial infarction (AMI), and the condition is associated with a 30-day mortality rate of up to 50%. Most of the AMI patients are in SCAI SHOCK stage B upon hospital arrival, but some of these patients will progression through the stages to overt shock (SCAI C-E). Around one third of patients who develop CS are not in shock at the time of hospital admission. Pro-B-type natriuretic peptide (proband) is a biomarker closely related to CS development. The aim of this study is to investigate the potential for preventing progression of hemodynamic instability by early inotropic support with low-dose dobutamine infusion administrated after revascularization in AMI patients with intermediate to high risk of in-hospital CS development. Methods This investigator-initiated, double-blinded, placebo-controlled, randomized, single-center, clinical trial will include 100 AMI patients (≥ 18 years) without CS at hospital admission and at intermediate-high risk of in-hospital CS development (ORBI risk score ≥ 10). Patients will be randomized in a 1:1 ratio to a 24 h intravenous (IV) infusion of dobutamine (5 μg/kg/min) or placebo (NaCl) administrated after acute percutaneous coronary intervention (PCI) (< 24 h from symptom onset). Blood samples are drawn at time points from study inclusion (before infusion, 12, 24, 36, and 48 h). The primary outcome is peak plasma proBNP within 48 h after infusion as a surrogate-measure for the hemodynamic status. Hemodynamic function will be assessed pulse rate, blood pressure, and lactate within 48 h after infusion and by transthoracic echocardiography (TTE) performed after 24–48 h and at follow-up after 3 months. Markers of cardiac injury (troponin T and creatine kinase MB (CK-MB)) will be assessed. Discussion Early inotropic support with low-dose dobutamine infusion in patients with AMI, treated with acute PCI, and at intermediate-high risk of in-hospital CS may serve as an intervention promoting hemodynamic stability and facilitating patient recovery. The effect will be assessed using proBNP as a surrogate marker of CS development, hemodynamic measurements, and TTE within the initial 48 h and repeated at a 3-month follow-up. Trial registration The Regional Ethics Committee : H-21045751. EudraCT: 2021–002028-19. ClinicalTrials.gov: NCT05350592, Registration date: 2022-03-08. WHO Universal Trial Number: U1111-1277–8523.